Effect of Hydrogen Content on the Microstructure, Mechanical Properties, and Fracture Mechanism of Low-Carbon Lath Martensite Steel - Boris Yanachkov; Yana Mourdjeva; Kateryna Valuiska; Vanya Dyakova; Krasimir Kolev; Julieta Kaleicheva; Rumyana Lazarova; Ivaylo Katzarov (Metals)
The effect of hydrogen content on the microstructure, mechanical properties, and fracture mechanisms of low-carbon lath martensitic steel was investigated using both experimental methods and atomistic modeling. Tensile testing revealed a transition in the fracture behavior with increases in hydrogen concentration. Specifically, at a hydrogen content of 0.44 wppm, a shift from transgranular to intergranular fractures was observed. The most probable cause of hydrogen embrittlement was identified to be HELP-mediated HEDE. As the hydrogen concentration increased, the dislocation density in close-packed planes, such as (111) and (100), was found to rise. The key differences between the hydrogen-free and hydrogen-charged specimens were the localization and density of dislocations, as well as the change in the distribution of slip bands. Atomistic modeling supported these experimental findings, showing that “quasi-cleavage” cracks predominantly initiate at block boundaries with higher local hydrogen accumulation. These results underscore the significant role of hydrogen in modifying both the microstructural characteristics and fracture behavior of low-carbon martensitic steel, with important implications for its performance in hydrogen-rich environments.